Internet en la lectura crítica en los estudiantes de décimo año de educación básica paralelos A, B, y C del Colegio Técnico Agropecuario UNE de la ciudad de Machala provincia de El Oro 2012. - Ruiz Cárdenas, Pedro Javier (2013)
The way how best abstracting information on the Internet through a comprehensive reading has become very important, because the reproduction of content by students, look for a tool and implemented in the teaching process also becomes undoubtedly some, the challenge in disciplinary teachers in traditional education.